Acupuncture for insomnia : sleep and dreams in Chinese medicine - Montakab, Hamid (Thieme, 2012)
[Publisher-supplied data] Insomnia and related sleep disorders concern 30-40% of the adult population and even up to 25% of children, affecting alertness and memory, causing emotional and physical fatigue, and putting the individual at increased risk for depression, cardiovascular disease, hypertension and other health hazards. Acupuncture for Insomnia: Sleep and Dreams in Chinese Medicine presents a highly effective treatment for chronic and acute sleeplessness using therapeutic strategies from both, TCM as well as Classical Chinese Medicine. Provides full background on the physiology, causes, and treatment of sleep disorders, drawing key parallels between concepts of Western and Chinese Medicine. Classifies all acupuncture points that affect sleep to help in choosing the most appropriate treatment for your patient. Offers a detailed analysis of sleep in Chinese Medicine to give you a full understanding of the energetics of sleep and wakefulness. Analyzes the significance of dreams in Chinese Medicine and how dreams can be skillfully integrated into a patients therapy. Written from the unique perspective of a physician who is also trained in TCM and classical acupuncture, this book presents numerous case examples, and an up-to-date review of scientific studies on Chinese medicine and sleep. It is an essential reference for all acupuncture practitioners who provide optimal treatment to patients with insomnia, sleep disorders, and other sleep pathologies.